2019
DOI: 10.1136/bmjopen-2018-028648
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes-specific health literacy and health-related quality of life among elderly individuals with pre-diabetes in rural Hunan Province, China: a cross-sectional study

Abstract: ObjectivesTo examine the association between diabetes-specific health literacy (DSHL) and health-related quality of life (HRQoL) among elderly individuals with pre-diabetes in rural China.Design, setting and participantsThis cross-sectional study included 434 elderly individuals with pre-diabetes from 42 villages in rural China.Main outcome measuresHRQoL was assessed using the Medical Outcomes Study 36-Item Short-Form Health Survey. DSHL was measured by a validated questionnaire in China. Differences in HRQoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
2
14
0
2
Order By: Relevance
“…The results of this study indicated that there was a significant relationship between educational level and quality of life; the quality of life in people with academic education was higher than other people. Similar to the results of this study, a study conducted by Hu showed that with elevation of the educational level, the quality of life in the physical and psychological dimensions increased significantly [49]. The educational level is an important factor in predicting quality of life, with increasing literacy level, quality of life increased significantly [50,51].…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study indicated that there was a significant relationship between educational level and quality of life; the quality of life in people with academic education was higher than other people. Similar to the results of this study, a study conducted by Hu showed that with elevation of the educational level, the quality of life in the physical and psychological dimensions increased significantly [49]. The educational level is an important factor in predicting quality of life, with increasing literacy level, quality of life increased significantly [50,51].…”
Section: Discussionsupporting
confidence: 84%
“…Improving health literacy is a strategic approach to preventing and controlling diseases [33]. Therefore, health professionals need to understand patients' health literacy before delivering interventions or education [34], in order to improve health-related quality of life [35,36].…”
Section: Backgroundsmentioning
confidence: 99%
“…14 One explanation is the low level of health literacy in Chinese patients with diabetes. Hu et al 15 accessed diabetes-specific health literacy in Chinese rural patients with diabetes using the Questionnaire of Health Literacy of Diabetes Mellitus of the Public in China was designed by the Chinese Center for Health Education, 16 and found that the average score was only 10.0, much less than the cut-off point of 19.5 defining the high or low health literacy level. The low health literacy and numeracy in Chinese patients greatly hindered the self-management implementation and effectiveness.…”
Section: What Are the New Findings?mentioning
confidence: 99%